Answer: [tex]8.493(10)^{-3} m/s[/tex]
Explanation:
According to the conservation of linear momentum principle, the initial momentum [tex]p_{i}[/tex] (before the collision) must be equal to the final momentum [tex]p_{f}[/tex] (after the collision):
[tex]p_{i}=p_{f}[/tex] (1)
In addition, the initial momentum is:
[tex]p_{i}=m_{1}V_{1}+m_{2}V_{2}[/tex] (2)
Where:
[tex]m_{1}=1.71(10)^{14} kg[/tex] is the mass of the comet
[tex]m_{2}=6.06(10)^{20} kg[/tex] is the mass of the asteroid
[tex]V_{1}=3.01(10)^{4} m/s[/tex] is the velocity of the comet, which is positive
[tex]V_{2}=0 m/s[/tex] is the velocity of the asteroid, since it is at rest
And the final momentum is:
[tex]p_{f}=(m_{1}+m_{2})V_{f}[/tex] (3)
Where:
[tex]V_{f}[/tex] is the final velocity
Then :
[tex]m_{1}V_{1}+m_{2}V_{2}=(m_{1}+m_{2})V_{f}[/tex] (4)
Isolating [tex]V_{f}[/tex]:
[tex]V_{f}=\frac{m_{1}V_{1}}{m_{1}+m_{2}}[/tex] (5)
[tex]V_{f}=\frac{(1.71(10)^{14} kg)(3.01(10)^{4} m/s)}{1.71(10)^{14} kg+6.06(10)^{20} kg}[/tex]
Finally:
[tex]V_{f}=8.493(10)^{-3} m/s[/tex] This is the final velocity, which is also in the positive direction.